Adab Berpakaian Wanita Muslimah Sesuai Tuntunan Syariat Islam - Syarifah Alawiyah; Budi Handrianto; Imas Kania Rahman (Rayah Al-Islam, 2020)
The phenomenon that afflicts Indonesian society, especially Muslim female students, is a culture of clothing that deviates from the guidance of Islamic law, although there are Muslim women who show how to dress according to Sharia, but the number is relatively small compared to those who are not. The phenomenon of wearing hijab is currently not in accordance with the requirements of Muslim women's clothing where not a few of the clothing models worn by women wearing hijab but still show the shape of the body, made from transparent and so on. Of course this is a problem that must be addressed by parents, educators and those in charge of education, because if it is left unchecked this will become a culture that will continue to develop and eventually become a law that is considered true by future generations. One way to overcome this is to raise awareness among Muslim women about the obligation to cover their genitals by providing sufficient understanding of genitals, the obligation to cover them and the adab of dressing in Islam. This study uses a literature review that synthesizes the theories and concepts of fiqh scholars about the aurat adab dress in Islam which then produces a concept of how to foster awareness of covering one's genitals which can be internalized in the form of dress behavior in Muslim women, especially students.